2023
DOI: 10.1021/jacs.3c00760
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Oxidation of Alcohols by a Luminescent Osmium(VI) Nitrido Complex: Evidence for the Generation of PhIO+ as a Highly Active Oxidant in the Presence of PhIO

Abstract: Although alcohols are readily oxidized by a variety of oxidants, their oxidation by metal nitrido complexes is yet to be studied. We report herein visible-light-induced oxidation of primary and secondary alcohols to carbonyl compounds by a strongly luminescent osmium(VI) nitrido complex (OsN). The proposed mechanism involves initial rate-limiting hydrogen-atom transfer (HAT) from the α-carbon of the alcohol to OsN*. Attempts to develop catalytic oxidation of alcohols by OsN* using PhIO as the terminal oxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In our previous work, we showed that OsN* readily undergoes an initial one-electron oxidation of various substrates, 12–16 hence it is reasonable to propose that the present photoreactions proceed via an initial 1 e − transfer (ET) from NCE − to OsN* to generate Os V N and the NCE˙ radical; this is followed by rapid recombination of the two species to afford the unstable intermediate [Os IV (L)(CN) 3 (N-ECN)] 2− , which then undergoes spontaneous E–CN bond cleavage to produce OsNE and CN − (Fig. 5).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous work, we showed that OsN* readily undergoes an initial one-electron oxidation of various substrates, 12–16 hence it is reasonable to propose that the present photoreactions proceed via an initial 1 e − transfer (ET) from NCE − to OsN* to generate Os V N and the NCE˙ radical; this is followed by rapid recombination of the two species to afford the unstable intermediate [Os IV (L)(CN) 3 (N-ECN)] 2− , which then undergoes spontaneous E–CN bond cleavage to produce OsNE and CN − (Fig. 5).…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, upon irradiation with visible light ( λ > 460 nm), OsN* readily activates the strong C–H bonds of alkanes and arenes, 11 undergoes oxidative N -dealkylation of various tertiary amines 12 and C–O bond cleavage of dihydroxybenzene, 13 exhibits formal N atom transfer to aliphatic secondary amines 14 and ring-nitrogenation of aromatic amines. 15 Recently, we have also found that OsN* could activate both α- and δ-C–H bonds of alcohols in the presence of PhIO, due to the formation of the highly potent oxidant PhIO + 16 (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%